Lack of local adaptation of invasive crofton weed (Ageratina adenophora) in different climatic areas of Yunnan Province, China - Zhao, X.; Liu, Wen-Yao; Zhou, M. (Oxford University Press, 2013)
Aims: Crofton weed, with a subtropical origin, has successfully invaded in diverse habitats that belong to different climate zones in Southwest China. We tested whether local adaptation plays an important role in the successful invasion of crofton weed in heterogeneous environments. Methods: Five populations from different habitats with an altitude ranging from 678 to 2356 m were selected. Plant height, biomass, seed yield and seed germination capability of these populations were investigated in the field. Greenhouse and reciprocal transplant experiments with the five populations were conducted, and all the above characters were measured and compared among these populations. Important Findings: Plant height, biomass, seed yield and seed germination rate were each significantly different among the five populations in field. However, there was no difference among these populations in the greenhouse experiment. In the reciprocal transplant experiment, plants from the five populations responded similarly to different habitats in the field, indicating lack of local adaptation. Instead, phenotypic plasticity likely plays a key role in the invasion success of crofton weed in different habitats.